2011
DOI: 10.1007/s10484-011-9163-0
|View full text |Cite
|
Sign up to set email alerts
|

Reward and Uncertainty Favor Risky Decision-Making in Pilots: Evidence from Cardiovascular and Oculometric Measurements

Abstract: In this paper we examined plan continuation error (PCE), a well known error made by pilots consisting in continuing the flight plan despite adverse meteorological conditions. Our hypothesis is that a large range of strong negative emotional consequences, including those induced by economic pressure, are associated with the decision to revise the flight plan and favor PCE. We investigated the economic hypothesis with a simplified landing task (reproduction of a real aircraft instrument) in which uncertainty and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 44 publications
3
23
0
Order By: Relevance
“…Our results showed that during the choices that posed no self-control dilemma the reaction times, fixation duration and number of gaze switches were higher compared to trials that did pose a self-control dilemma. It is well established that reaction times, fixation durations and number of gaze switches are higher in difficult tasks requiring the recruitment of cognitive resources (Panayiotou and Vrana, 2004; Causse et al, 2011). Furthermore, a cluster in the anterior cingulate cortex, which has previously been shown to activate during the perception of conflict (Botvinick et al, 2001; van Veen et al, 2001), was more strongly activated during trials that did not pose a self-control dilemma (NSC trials).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our results showed that during the choices that posed no self-control dilemma the reaction times, fixation duration and number of gaze switches were higher compared to trials that did pose a self-control dilemma. It is well established that reaction times, fixation durations and number of gaze switches are higher in difficult tasks requiring the recruitment of cognitive resources (Panayiotou and Vrana, 2004; Causse et al, 2011). Furthermore, a cluster in the anterior cingulate cortex, which has previously been shown to activate during the perception of conflict (Botvinick et al, 2001; van Veen et al, 2001), was more strongly activated during trials that did not pose a self-control dilemma (NSC trials).…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, implicit measures are less susceptible to demand characteristics and socially desirable responding (Fazio and Olson, 2003) than self-reported measures. Thirdly, ACC activity, reaction times, and fixation durations are well acknowledged measures to investigate response conflict (Kawashima et al, 1996; Macdonald et al, 2000; Botvinick et al, 2001; van Veen et al, 2001; Kerns et al, 2004; Panayiotou and Vrana, 2004; Causse et al, 2011). Finally, explicitly asking for response conflict during the food choices focusses attention on conflict which may also affect their choice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Three attentional tunneling metrics were employed in this study: the HR, the number of AOI (NBAOI) glanced at on the user interface, and the switching rate (SWR). The literature suggests that HR increases with psychological stress [28]- [34], and NBAOI and SWR decrease with attentional tunneling [17], [18]. The calculation of the Fig.…”
Section: Present Studymentioning
confidence: 99%
“…Participants from the TUN = 1 group were highly focused on the demanding identification task during S4 as revealed by the decrease of the NBAOI and SWR. Their inability to successfully perform this critical task generated stress [39], associated with the higher HR during S4 [28]- [34]. Conversely, participants from the TUN = 0 group did not faced such stress.…”
Section: B Inferential Analysis Of the Input Raw Datamentioning
confidence: 99%